Pengembangan Media Pembelajaran berbasis Android untuk Materi Pemrograman Dasar di SMK Negeri 5 Malang - Mochammad Hafidz; Wibisono Sukmo Wardhono; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
How easy access to learning media in a smartphone will make students often accessing the available media to increase students learning interest and learning results. "Pemrograman Dasar Portabel" is an Android learning media that is developed for improving learning interest and learning result at SMK Negeri 5 Malang. This media is developed with waterfall method because of clear needs. This media is made using Adobe After Effect for the learning materials and Android Studio for the application. The result from the research shows that the learning interest of students after using the media shows the value of 83,2 that shows a high category, in detail, there are seventeen students or 68% have very high learning interest, seven students or 28% have high learning interest and one student or 4% have low learning interest. Students learning results in the pre-test have a mean value of 45,6 and the post-test has a result of 73,6. Based on the Wilcoxon test result, a found value of 0,000 which means the improvement of the learning result after using media is improved significantly.